Pre-exposure prophylaxis (PrEP) for HIV prevention in Eswatini: understanding the barriers, facilitators and opportunities for women - Bärnighausen, Kathryn (University of the Witwatersrand, Johannesburg, 2024)
In 2015 the World Health Organization confirmed the efficacy and safety of pre-exposure prophylaxis (PrEP) and recommended PrEP for use within populations at high risk of HIV acquisition. In Eswatini – the country with the highest incidence and prevalence globally – the Eswatini Ministry of Health, in partnership with Clinton Health Access Initiative (CHAI), designed a demonstration project which aimed to understand what was needed to successfully introduce PrEP into a national HIV prevention programme for the general population at risk for HIV. Here, using a PrEP prevention cascade to organise our findings, this thesis presents the content of five peer reviewed research articles which stem from a formative qualitative research component built within the demonstration project. Between 2017 and 2020 there were two rounds of rigorous data collection, including 217 semi-structured in-depth interviews, with adult (>18 years) Health Care Workers (HCWs) providing PrEP, relevant stakeholders and PrEP uptake, decline, discontinuation and continuing PrEP clients in Eswatini. Using a constructivist grounded theory approach, this thesis describes qualitatively where – along the cascade – gaps in service provision, demand creation, access, and retention in care for women (and others) are visible. The thesis highlights adaptations made by HCWs and recommendations from participants to address these gaps. The thesis describes the developed and adapted theoretical models we use to demonstrate where resilience can be used to create demand for PrEP, the structural, policy, community, personal and inter-personal levels that influence PrEP uptake, decline, continuance and discontinuance, and how a prevention-effective-adherence approach to PrEP could save resources, limit adherence burdens and mitigate negative perceptions related to stopping and starting PrEP. The work demonstrates the need for community-based demand creation, the inadequacies of the PrEP Promotion Package (PPP), and where changes were made to the PPP based on the analysis and interpretation of our data. While the findings have informed the successful national scale up of PrEP in Eswatini and have contributed to positive programmatic and implementation adaptations, it is also clear how PrEP clients – those most at risk of HIV infection – lie at the intersections of poverty, vulnerability, injustice and inequality. Ensuring the effectiveness of PrEP and the prevention of HIV acquisition requires multilevel approaches that extend far beyond a prevention cascade, and need to consider and incorporate the lived experiences of those in Eswatini and other high incidence settings globally.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, in the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; PrEP; qualitative; SDG-3: Good health and well-being